Law Enforcement in Indonesia in Perspective of Transcendental Legal Justice Paradigm - Siti Kasiyati (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2020)
Law enforcement in Indonesia still leaves various problems, especially regarding the sense of justice. Such as diffable cases dealing with the law, civil cases, especially in the land sector, which relies on property rights certificates, cases of domestic violence (nusyuz).In this case, this study discusses how law enforcement in Indonesia is, and how law enforcement is in the perspective of the transcendental justice paradigm. This research is a literary research using secondary data sources, namely primary and secondary legal materials. This study includes a normative study with a synthetic analytic approach.Based on the results of the analysis, law enforcement in Indonesia, both criminal and civil, is still fixated on legal certainty, thus ignoring substantive justice. This is where a shift is needed from the paradigm of law enforcement based on legal certainty to transcendent justice. This condition can be seen from several decisions that are very formalistic and based on laws, where legal certainty is the front line compared to substantive justice so that justice is not felt by the public. This condition is also strongly influenced by the legal paradigm adopted in Indonesia, namely positivist law or known as the systemic legal paradigm. Transcendental starts from irrational and metaphysical thinking such as emotions, feelings, instincts, moral spirituality and as part of building science. In this context, law enforcement. The perspective of the transcendental legal justice paradigm highlights how the purpose of Islamic law is useful for justice and human welfare. Where the law is based on ethics (morals) so that it can produce substantive justice, not mere formalistic justice, which summarizes the human attitude to be fair to God as the creator, fair to fellow humans and fair to the universe.